(untitled) (BIRDEM Medical Journal, 2018)
Background: Infertility refers to inability to achieve conception even after one year of unprotected coitus by a couple. It is a global health problem and affects 8-10% couple worldwide. Infertility can be primary or secondary and there are many causes of infertility involving both male and female partner. A wide range of investigations can be done to find out the causes of infertility. Endometrial biopsy or curettage or aspiration followed by histopathological study is a safe procedure. It not only shows the hormonal response of endometrium but also diagnose other endometrial pathology causing infertility. The study was performed to find out the morphological pattern of endometrium in infertile women in a tertiary care hospital to find out the causes of infertility and subsequent treatment of the patients. Methods: It was a cross sectional prospective study, conducted in the Department of Histopathology and Cytopathology in a tertiary care hospital in Dhaka for a period of two years from Jan 2015 to Dec 2016. It included 196 referred cases endometrial curettage or biopsy samples of infertile women, collected between days 21 to 23 of menstrual cycle. The endometrial samples obtained from patients suffering from diseases other than infertility were excluded from the study. Hematoxylin and Eosin (H&E) stained histopathological slides were prepared from the samples and examined under microscope. Reported results and relevant data were recorded in SPSS data collection sheet and statistical analysis was carried out. Results: A total of 196 cases of endometrial biopsy or curettage samples of both primary and secondary infertile women were studied. Age ranged from 20 years to 40 years with a mean age of 29.91±4.32years. 70.92% cases presented with primary infertility and 29.08% cases presented with secondary infertility. Proliferative phase/anovulation (41.33%) was found as the most common morphological pattern of endometrium in infertile women followed by secretory phase (40.30%). Endometrial hyperplasia, inadequate sample, nonspecific ednometritis and tuberculous endometritis were found in 10.72% , 6.12% , 6.12% and 0.51% cases respectively. In primary infertility, proliferative phase / anovulation (43.17%) was also the predominant pattern followed by secretory phase (37.40%) and endometrial hyperplasia (11.52%). Whereas, secretory phase( 47.37%) was the most common pattern of endometrium in secondary infertility, followed by proliferative phase (36.37%) and endometrial hyperplasia (8.77%). Primary infertility was most frequently presented in 26-30 years of age, whereas, secondary infertility was more prevalent in later age group. Conclusion: Histopathological study of endometrium gives us valuable information of endometrium in infertility. Morphological pattern of endometrium in our study was quite similar to other studies conducted in different countries with some variations. This study may help other studies in future to find out the cause of infertility Birdem Med J 2018; 8(2): 132-137